PENGEMBANGAN MODEL PEMBELAJARAN DENGAN VISUALISASI UNTUK MATERI PENAMAAN, PENOMORAN DAN PENJAJARAN GUNA PENINGKATAN KOMPETENSI DI BIDANG REKAM MEDIS - Trismianto Asmo Sutrisno; Erna Zakiyah (PSTE UNIMUS, 2014)
This research aimes to develop a model of learning system by visualization for material specifically naming, numbering and filing is useful to improve the quality of competence in the field of medical records.The development model of learning system with visualization is expected to provide an overview of the implementation of naming system, numbering system and filing system in the field of medical records at health care units (such as hospitals or public health centers), so the expected competencies can be achieved.This research approach using the System Development Life Cycle using Waterfall models. Software development is implemented by stages: 1) software requirements analysis, 2) design, 3) coding and 4) testing.This research has successfully produced a model of learning system with visualization, especially for material naming, numbering and filing in the case study on the Diploma Program of Medical Records and Health Information at Health Polytechnic “Bhakti Mulia Sukoharjo” in Central Java. Learning model for naming system is divided into two material, the index of patient's name and the sorting of patient's name. Keywords: a model of learning system, medical records, naming system, numbering system, filing system